IMPLIKASI KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Augustpaosa Nariman (Universitas Kristen Krida Wacana, 2019)
Earnings owned by the company will attract investors to invest their capital in the company. Increased profits will have an impact on increasing the value of the company as seen from the company’s stock market price. The increasing value of the company will be influenced by several factors, namely financial performance, debt policy and intellectual capital. Financial performance illustrates how much companies can get profits, and how much the rate of return on equity. Financial performance is illustrated through profitability ratios. Debt policy is how much a company uses debt as a company capital in running its business. Intellectual capital is a non-physical factor that can provide benefits to the Company. In this case, it is illustrated by the company’s ability to develop technology, the ability and commitment of employees in carrying out their work and the system of procedures established by the company in carrying out its operational activities. The purpose of this study is to analyze how the influence of financial performance, debt policy, and intellectual capital on firm value. This study uses secondary data from manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. By using purposive sampling techniques and in accordance with predetermined criteria. The results showed that financial performance had a significant positive effect, debt policy had a significant negative effect, and Intellectual capital had no significant effect on the company. The analysis shows that financial performance and intellectual capital have a positive relationship, which when the financial performance and intellectual capital increase, there will be an increase in the value of the company, while debt policy shows a negative relationship, which debt policy ratio increases, there will be a decrease in the value of the company.Keywords: Financial Performance, Debt policy, Intellectual Capital, Value of the firm